Application of 2-Trichloromethylbenzimidazole in Analytical Chemistry: A Highly Selective Chromogenic Reagent for Thin-Layer Chromatography and Some Other Analytical Uses - Leszek Konopski; Anna Kiełczewska (Journal of Analytical Methods in Chemistry)
2-Trichloromethylbenzimidazole (TCMB) was used as a chromogenic reagent in organic or inorganic analysis, mainly in thin-layer chromatography (TLC). In reactions of TCMB with some heteroaromatic nitrogen containing compounds, such as azines, azoles and benzazoles, a formation of high colored products occurred. For azines, the chromogenic reaction was highly regioselective, since the both adjacent α-positions versus the nitrogen atom(s) must not be substituted. A TLC method of detection was developed. Thirty azines, azoles, and benzazoles were detected at the detection limit 10 ng to 1 μg. This method was also applied for detection of heteroaromatic pesticides, and the attempts to construct active and passive dosimeters for nicotine were made. In a prechromatographic reaction of aromatic o-diamines with methyl trichloroacetimidate, TCMB or its derivatives were formed in situ. Followed by TLC and visualization in pyridine vapors, this procedure was applied for detection of o-phenylenediamine derivatives. The reaction product of TCMB and pyridine (LI Complex) was identified and fully characterized. Two different reaction mechanisms: with electron deficient basic heteroaromatic compounds, like pyridine, and with more acidic compounds, for example, pyrrole, were discussed. In aqueous solutions, the LI Complex may be also used as a new indicator for complexometric, adsorption and acid-base titration of inorganic compounds.